The human-animal interaction at work scale: Development and psychometric properties - Junça Silva, A. (Journal of Veterinary Behavior, 2024)
This study aimed to develop and validate the Human-Animal Interaction at Work Scale (HAI@WS). This instrument is designed to measure human-animal interactions during work time. We conducted four studies to achieve this goal. First, we developed the scale, followed by a study to explore its factorial structure (N = 1013). The third study analyzed the scale's internal validity and reliability (N = 253). The fourth study was a daily-diary investigation that assessed the criterion validity of the HAI@WS by examining its within-person correlations with measures of performance, satisfaction, and work engagement (N = 145 × 5 = 725). The findings revealed that the three-item scale represented a single factor and is a reliable measure of human-animal interactions in the work context. Additionally, the results indicated that the scale was significantly related to measures of performance, satisfaction, and work engagement at the within-person level. This study fills a research gap by providing a validated measure for assessing human-animal interactions in the workplace, an area previously lacking such tools. The HAI@WS is valuable for managers seeking to evaluate how the presence of pets at work—whether during teleworking or in the office—and the resulting interactions with employees can satisfy biological and psychological needs, thereby promoting positive outcomes such as work engagement and positive affective work-related experiences. This research advances our understanding of human-animal interactions and their impact on individuals and organizations.